Organizational tools for overcoming the systemic contradictions of innovative development - Kiseleva, Natalia N.; Bozieva, Irina A.; Lyapuntsova, Elena V.; KlimovаNatalia V.; Grigorieva, Lyudmila V. (Opción, 2019)
The article discusses the systemic contradictions of innovative development of the Russian economy, which have proved very difficult to overcome either by market, state/corporate, management tools or planning. The methodological basis of the research is the principles of dialectical logic, which presuppose the consideration of the economy as a multifaceted category with objective and subjective characteristics. As a result, it becomes necessary to form new economic relations corresponding to the challenges of the knowledge economy. In conclusion, the integration of all the requirements is possible only within the framework of conceptualization and effective implementation of a national innovative digital platform.